2017
DOI: 10.3928/23258160-20170802-05
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Positive Endophthalmitis After Open Globe Injuries With and Without Retained Intraocular Foreign Bodies

Abstract: Culture-positive endophthalmitis was identified after OGIs more often in eyes with a concurrent IOFB. [Ophthalmic Surg Lasers Imaging Retina. 2017;48:632-637.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
6
18
0
2
Order By: Relevance
“…Intraocular antibiotics has been shown by metaanalysis to reduce the risk of traumatic endophthalmitis [20]. While several centers routinely use prophylactic systemic antibiotics [5,21,22], their use is controversial without strong supporting evidence [7]. Intravenous antibiotics were not advantageous over oral prophylaxis in a randomized controlled trial [6]; however, systemic antibiotics have not been compared with local administration in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraocular antibiotics has been shown by metaanalysis to reduce the risk of traumatic endophthalmitis [20]. While several centers routinely use prophylactic systemic antibiotics [5,21,22], their use is controversial without strong supporting evidence [7]. Intravenous antibiotics were not advantageous over oral prophylaxis in a randomized controlled trial [6]; however, systemic antibiotics have not been compared with local administration in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Endophthalmitis is a potentially devastating sequela of open globe injury. Rates of endophthalmitis after severe ocular trauma range from 0 to 17% [2,3], with a higher risk in the presence of an intraocular foreign body (IOFB) [4,5]. Outcomes are typically worse than post-operative endophthalmitis [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have described series of posttraumatic endophthalmitis and the distribution of isolates worldwide [1,6,10,11]. ese studies showed that the susceptibilities of microbiological isolates and infectious agents to particular antibiotics varied over time and differed according to regional variability, population, and ethnicity [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Endophthalmitis is a devastating clinical condition that can lead to severe visual loss. [1][2][3][4] Previous research reported that the incidence rate of infectious endophthalmitis following intraocular foreign body (IOFB) injuries ranged from 6.9-30% [5]. IOFB injuries were reported in 43% of posttraumatic endophthalmitis cases [6].…”
Section: Introductionmentioning
confidence: 99%
“…Trauma accounts for up to 25–30′ of infectious endophthalmitis [7]. In reported large series, the incidence of endophthalmitis after open globe injury generally ranges from 3 to 5′ [11, 12, 13, 14, 15, 16, 17, 18, 19] and may be higher in the setting of soil contamination [20]. As O. turbata is found in soil and grass cuttings [21], this patient demonstrates that atypical organisms must be considered in chronic, indolent endophthalmitis when the infection source is known to be organic matter [22, 23].…”
Section: Discussionmentioning
confidence: 99%